Ultrasonic and thermodynamic effects of self-association of aliphatic alcohols in c-C6H12. II. Primary and tertiary pentanols - BEBEK, K.; MANIKOWSKI, R.; ERNST, S. (Archives of Acoustics, 1993)
The ultrasound velocities in and densities of mixtures of cyclohexane with n-pentanol {x_1n-C5H11OH + (1-x_1)C6H12} and with 2-methylbutan-2-ol {x_1tert- C5H11OH + (1-x_1)C6H12} have been measured at 293.15 K. Using the measurement results in connection with the literature data, the following quantities have been determined: isothermal and adiabatic compressibility coefficients, β_T = -1/V(∂V/∂p)T and β_s = -1/V(∂V/∂p)_s, respectively, the adiabatic compressibility, ϰ_s = -(∂V/∂p)_s, the free intermolecular length, L, and the excess values of the molar volume, V^E, of the adiabatic compressibility coefficient, β^e_S, and of the adiabatic compressibility, ϰ^E_s. The dependences of those excess functions on the mixture composition, expressed in mole fractions, were represented by Redlich-Kister equations.